Kingston Adopts the Telephone: The Social Diffusion and Use of the Telephone in Urban Central Canada, 1876 to 1914 - Pike, Robert (Urban History Review / Revue d'histoire urbaine, 1989)
The adoption and use of the telephone in urban central Canada between 1876 and 1914 are explored within the context of the wider communications environment and the marketing strategies of the Bell Telephone Company. This context becomes the framework for a case study of the social diffusion of the telephone in Kingston, Ont, between 1883 and 1911. Utilizing telephone directories and early city directories, the case study concentrates on the socioeconomic and organizational characteristics of early phone subscribers and the physical location of their phones. Both business and residential subscribers are shown throughout the period to have been drawn mainly from the commercial and prof essional classes in Kingston and to have used the phone mainly for institutional, work-related purposes.